Government Revenue and Government Spending Nexus: A Testing Hypothesis for Indonesia - Akhmad Solikin; Muhammad Afdi Nizar (Jurnal Borneo Administrator, 2023)
There are still differences of opinion about the connection between government expenditure and revenues. This study aims to test hypotheses related to the direction of the relationship between Indonesian government revenues and expenses. By utilizing quarterly time-series data in the period 1969: q2 – 2020: q4, the test was implemented using the Vector Autoregressive (VAR) model. The test results show that an increase in total government revenue and tax revenue causes an increase in government spending during the study period. The results of this study provide supporting evidence for the revenue-and-expenditure or tax-and-spending hypothesis for the Indonesian government budget. The implication is that the government budget is always in deficit, and the need for financing (i.e., loans) is unavoidable